2003
DOI: 10.1523/jneurosci.23-04-01340.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of C-Terminal Cytoplasmic Tail of Rat Vanilloid Receptor 1

Abstract: The vanilloid receptor [transient receptor potential (TRP)V1, also known as VR1] is a member of the TRP channel family. These receptors share a significant sequence homology, a similar predicted structure with six transmembrane-spanning domains (S1-S6), a pore-forming region between S5 and S6, and the cytoplasmically oriented C- and N-terminal regions. Although structural/functional studies have identified some of the key amino acids influencing the gating of the TRPV1 ion channel, the possible contributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
168
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 43 publications
12
168
0
1
Order By: Relevance
“…Both TRPV1 ctV3 and ctV3(B) showed reduced ⌬H°, suggesting that the altered heat sensitivity of ctV3 and ctV3(B) is commonly derived from the alteration of the distal half of CTD. Altered heat sensitivity conferred by truncation of the distal half of the CTD has been reported in rat TRPV1 and in tissue-specific splicing variants of TRPV1 in vampire bats (28,39,40). In contrast to activation, TRPV1 ctV3(B) displayed heat-induced desensitization similar to WT, whereas ctV3 lacked heat-induced desensitization.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Both TRPV1 ctV3 and ctV3(B) showed reduced ⌬H°, suggesting that the altered heat sensitivity of ctV3 and ctV3(B) is commonly derived from the alteration of the distal half of CTD. Altered heat sensitivity conferred by truncation of the distal half of the CTD has been reported in rat TRPV1 and in tissue-specific splicing variants of TRPV1 in vampire bats (28,39,40). In contrast to activation, TRPV1 ctV3(B) displayed heat-induced desensitization similar to WT, whereas ctV3 lacked heat-induced desensitization.…”
Section: Discussionmentioning
confidence: 94%
“…It is unclear how the distal end of the CTD affects heat-induced desensitization. A previous molecular modeling study based upon the structure of a homologous protein predicted that the distal end of the CTD contains an ␣-helical structure (28). We assume that the presumptive ␣-helix may be involved in heat-induced desensitization, which is affected by truncation of the C⌬7 segment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We did not identify the relevant residues in this region due to the relatively small size of the effect, however, other studies have shown that amino acids in the N-and C-terminal tails can affect capsaicin binding and function (26,27).…”
Section: Discussionmentioning
confidence: 99%